2009
DOI: 10.2478/s11756-009-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spruce forest on rainfall interception and seasonal snow cover evolution in the Western Tatra Mountains, Slovakia

Abstract: The paper analyzes the impacts of the spruce forest on precipitation interception and evolution of snow cover in the mountain catchment of the Jalovecký creek, the Western Tatra Mountains, Slovakia. Both processes were monitored at the elevation of 1420 m a.s.l. . Interception was measured from the end of August 2006 until November 2008 by a network of 13 raingauges. Mean interception over the studied period in forest window was 23%. Mean values for the dripping zone under tree branches, near stems of the tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 5 publications
2
35
0
Order By: Relevance
“…The data have been used in a number of studies devoted to various aspects of snow hydrology (Holko et al, 2011) including climate change and vegetation impacts (Holko et al, 2009b;Kostka and Holko, 2000), modelling (Holko et al, 2003(Holko et al, , 2009a, remote sensing Krajčí et al, 2014) and isotopic studies (Holko et al, 2013;Penna et al, 2014).…”
Section: Materials and Methods Study Areamentioning
confidence: 99%
“…The data have been used in a number of studies devoted to various aspects of snow hydrology (Holko et al, 2011) including climate change and vegetation impacts (Holko et al, 2009b;Kostka and Holko, 2000), modelling (Holko et al, 2003(Holko et al, , 2009a, remote sensing Krajčí et al, 2014) and isotopic studies (Holko et al, 2013;Penna et al, 2014).…”
Section: Materials and Methods Study Areamentioning
confidence: 99%
“…The snow interception affects snow accumulation under treetops (Garvelmann et al, 2013;Holko et al, 2009;Stähli et al, 2009;Strasser et al, 2011). Additionally, the forest influences turbulent fluxes (Pohl et al, 2006) and reduces the amount of short-wave solar radiation and thus snowmelt rates (Pomeroy et al, 2012;Schnorbus and Alila, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Throughfall was measured by the tipping bucket gauge in the nearby mature forest spruce (mean age 110 years). Our previous measurements on the site using a number of manually operated rain gauges (Holko et al, 2009) revealed high variability of interception even at the same typical locations (forest window, dripping zone, near stem zone). Therefore, the tipping bucket rain gauge used in this study was placed into a forest window which showed the smallest spatial variability of throughfall in the previous study.…”
Section: Description Of Study Area and Measured Datamentioning
confidence: 77%
“…The study strives to supplement the results of numerous studies conducted in the Western Carpathians by foresters and hydrologists (e.g. Zelený and Tichý, 1968;Majerčáková, 1983;Benetin et al, 1986;Valtýni, 1986;Tužinský, 1995;Lančarič et al, 2001;Minďáš, 2001;Pekárová et al, 2005, Halmová et al, 2006Miklánek et al, 2006;Holko et al, 2009) by focusing on the shorttime resolution (10-minutes) rainfall and throughfall data in a high-mountain forest.…”
Section: Introductionmentioning
confidence: 95%